Method for producing R-T-B system sintered magnet
By using the heat treatment technology of R2-M alloy powder and R1-T-B system sintered magnet raw material produced by the atomization method, the HcJ and Br of R-T-B system sintered magnets are improved without using Dy and Tb. Problem, high bonding strength and suitable for high-speed rotating motors are achieved.
Patent Information
- Application Number
- CN201980023692.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-20
- Filing Date
- 2019-02-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2039-02-22
AI Technical Summary
The prior art is difficult to increase the coercive force HcJ of the R-T-B system sintered magnet without using Dy and Tb, and in applications such as high-speed rotating motors, new technologies with high bonding strength are needed.
The R1-T-B-type sintered magnet raw material containing rare earth elements of Nd and Pr, and the R2-M alloy powder prepared by atomization method is heat treated to achieve high bonding strength. The R2-M alloy powder contains more than 65% R2 and more than 3% or less metal element M, such as Ga, for example, to increase HcJ and Br of magnets.
It realizes R-T-B system sintered magnets with high Br and HcJ without using Dy and Tb, and improves bonding strength, and is suitable for applications such as high-speed rotating motors and other applications.
Smart Images

Figure CN111937103B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing an R-T-B system sintered magnet. Background Art
[0002] R-T-B sintered magnets (R is at least one of the rare earth elements and must contain Nd. T is Fe or Fe and Co, and B is boron) are known to be the highest performance magnets among permanent magnets. They are used in various motors and home appliances such as voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV, etc.), motors for industrial equipment, etc.
[0003] R-T-B series sintered magnets mainly consist of R2T 14 The main phase of the B compound and the grain boundary phase located at the grain boundary of the main phase. 14 B compound is a ferromagnetic material with high saturation magnetization and anisotropic magnetic field, which is the basis of the characteristics of R-T-B system sintered magnets.
[0004] At high temperatures, due to the coercive force H of R-T-B sintered magnets cJ (Hereinafter, sometimes referred to as “H cJ Therefore, high H is required in R-T-B sintered magnets, especially for electric vehicle motors. cJ .
[0005] It is known that in R-T-B based sintered magnets, heavy rare earth elements RH (such as Dy and Tb) are used to replace R2T 14 When a part of the light rare earth element RL (e.g. Nd, Pr) contained in R in the B compound is cJ As the amount of RH replacement increases, H cJ improve.
[0006] However, replacing R2T with RH 14 When RL in B compound, H of R-T-B sintered magnet cJ On the other hand, the residual flux density B r (hereinafter, sometimes referred to as "B r ”) decreased. In addition, heavy rare earth elements such as Dy and Tb have problems such as unstable supply and large price fluctuations due to the small resource reserves and limited production areas. Therefore, in recent years, it is required to reduce the use of heavy rare earth elements such as Dy and Tb as much as possible and increase H cJ .
[0007] In order to suppress the use of heavy rare earth elements, Patent Document 1 discloses a technology that requires increasing H cJThe unit magnets are configured with a relatively high content of heavy rare earth elements such as Dy in some parts and a relatively low content of heavy rare earth elements in other parts, and these multiple unit magnets are joined. The joint surfaces of the unit magnets are heated in a contact state using a paste made by mixing metal powder containing heavy rare earth elements and organic matter.
[0008] Patent Document 2 discloses a technology for joining dissimilar material components such as an R-T-B rare earth sintered magnet and a silicon steel plate using alloy powder of a rare earth element and other metal elements.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2015-73045
[0012] Patent Document 2: Japanese Patent Application Laid-Open No. 8-116633 Summary of the invention
[0013] Technical problem to be solved by the invention
[0014] By using the bonding technology disclosed in Patent Document 1, the amount of heavy rare earth elements used can be reduced by configuring unit magnets having a relatively high content of heavy rare earth elements such as Dy and unit magnets having a relatively low content of heavy rare earth elements. However, the bonding surfaces of the unit magnets are bonded by heating a paste made by mixing metal powder containing heavy rare earth elements and organic matter in a contact state (i.e., bonding is achieved by diffusion of the heavy rare earth elements).
[0015] In recent years, in applications such as electric vehicle motors, high H is required even without using Dy and Tb. cJ In addition, the joining techniques disclosed in Patent Documents 1 and 2 can join R-T-B rare earth sintered magnets to each other or to iron-based metal parts. However, according to the results of the present inventors' research, when used in electric motors that require high-speed rotation, a new joining technique that can achieve high joining strength is required.
[0016] Each embodiment of the present invention provides a method for achieving high bonding strength and having high B even without using Dy and Tb. r and high H cJ A method for producing an R-T-B sintered magnet.
[0017] Technical solutions for solving technical problems
[0018] In the illustrated embodiment, the manufacturing method of the R-T-B system sintered magnet of the present invention includes: a process of preparing a plurality of R1-T-B system sintered magnet raw materials (R1 is a rare earth element containing at least one of Nd and Pr) having different compositions; a process of preparing an R2-M alloy powder containing 65 mass % to 97 mass % of R2 (R2 is a rare earth element containing at least one of Nd and Pr, and the total content of Dy and Tb is 50 mass % or less relative to all R2) and 3 mass % to 35 mass % of M (M is at least one selected from Ga, Cu, In, Al, Sn and Co) and produced by an atomization method; and a process of arranging the above-mentioned R2-M alloy powder between the above-mentioned plurality of R1-T-B system sintered magnet raw materials and joining the above-mentioned plurality of R1-T-B system sintered magnet raw materials at a temperature of 450°C to 1000°C.
[0019] In one embodiment, the total content of Dy and Tb is 15 mass % or less based on the total R2.
[0020] In a certain embodiment, R2 must include Pr, and M must include Ga.
[0021] In one embodiment, the plurality of R1-TB system sintered magnet materials include a first R1-TB system sintered magnet material having a relatively high coercive force and a second R1-TB system sintered magnet material having a relatively low coercive force.
[0022] In one embodiment, at least one of the first R1-TB system sintered magnet material and the second R1-TB system sintered magnet material has a thickness of 2 mm or less.
[0023] In one embodiment, at least one of the first R1-TB system sintered magnet material and the second R1-TB system sintered magnet material has a thickness of 1 mm or less.
[0024] Effects of the Invention
[0025] According to the embodiment of the present invention, since the bonding is performed using the R2-M alloy powder produced by the atomization method, it is possible to produce a high bonding strength and a high B without using Dy and Tb. r and H cJ R-T-B sintered magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1A This is a cross-sectional view schematically showing an enlarged portion of an RTB based sintered magnet.
[0027] Figure 1B Yes Figure 1AThe dotted rectangular area is further enlarged and schematically shown in the cross-sectional view.
[0028] Figure 2 This is a schematic cross-sectional view of a conventional alloy powder formed by pulverization.
[0029] Figure 3 This is a schematic cross-sectional view of an alloy powder formed by an atomization method according to an embodiment of the present invention.
[0030] Figure 4 It is a perspective view schematically showing a state of R1-TB based sintered magnet materials before joining according to an embodiment of the present invention.
[0031] Figure 5 It is a perspective view schematically showing a state in which R1-TB based sintered magnet materials are being joined according to an embodiment of the present invention.
[0032] Figure 6 This is a flowchart showing an example of the process of the method for producing an RTB based sintered magnet according to the embodiment of the present invention. DETAILED DESCRIPTION
[0033] Figure 1A This is a cross-sectional view schematically showing an enlarged portion of an R-TB system sintered magnet. Figure 1B Yes Figure 1A The cross-sectional view is further enlarged and schematically shown in the dotted rectangular area. Figure 1A For reference, as an example, an arrow with a length of 5 μm is recorded as the length of the reference for indicating the size. Figure 1A and Figure 1B As shown in the figure, R-T-B sintered magnets are mainly composed of R2T 14 The main phase 12 of the B compound and the grain boundary phase 14 located at the grain boundary of the main phase 12 are composed. Figure 1B As shown, the grain boundary phase 14 contains two R2T 14 The grain boundary phase 14a and three R2T phases between two adjacent B compound particles (grains) 14 The grain boundary triple point 14b between adjacent B compound particles.
[0034] R2T as the main phase 12 14 B compound is a ferromagnetic material with high saturation magnetization and anisotropic magnetic field. Therefore, in R-T-B system sintered magnet, by increasing the R2T 14 The presence ratio of B compound can increase r To improve R2T 14 The ratio of the B compound is as long as the amount of R, T, and B in the raw alloy is close to R2T 14The stoichiometric ratio of the B compound (R amount: T amount: B amount = 2:14:1) is sufficient.
[0035] The present inventors have found that by diffusing R and at least one selected from Ga, Cu, In, Al, Sn and Co into the grain boundaries, the grain boundary phase can be modified to increase the H cJ . In such a modification of the grain boundary phase, it is preferred to prepare an R1-T-B system sintered magnet raw material (R1 is a rare earth element containing at least one of Nd and Pr), supply a metal element M (at least one selected from Ga, Cu, In, Al, Sn and Co) from the surface of the R1-T-B system sintered magnet raw material to the grain boundary, and diffuse it in the grain boundary. Such diffusion of the metal element M can be carried out using an alloy of 65 mass % to 97 mass % of R2 (a rare earth element containing at least one of Nd and Pr) and 3 mass % to 35 mass % of M, i.e., a powder of an R2-M alloy. In this way, a material having a high B even without using Dy and Tb can be obtained. r and high H cJ R-T-B sintered magnet.
[0036] According to the results of further research conducted by the inventors, it is known that when a heat treatment is performed to apply R2-M alloy powder (atomized powder of R2-M alloy) produced by atomization method on the surface of R1-T-B system sintered magnet raw materials and diffuse it, it can be used as an excellent flux for joining other individual parts to R1-T-B system sintered magnet raw materials. That is, it is known that the atomized powder of R2-M alloy can function as a diffusion source for introduction into the grain boundary of two particles, and also function as a powder for joining and uniformly bonding the surfaces of R1-T-B system sintered magnets. This is because the shape and size distribution of the particles of the atomized powder are uniform compared to the powder particles formed by pulverizing the R2-M alloy. As a result, pores are less likely to form on the joining surface, and the joining strength is improved.
[0037] Figure 2 This is a schematic cross-sectional view of an alloy powder 50 formed by conventional pulverization (e.g., a method of pulverizing a raw alloy after making it by an ingot casting method or a thin strip continuous casting method). The alloy powder is disposed between two solid components 20 and is located in a gap formed by the opposing surfaces (joined surfaces) 20S of the components 20. Figure 2 It can be seen that the shapes and sizes of the individual powder particles 50P are random. The alloy powder 50 is produced by pulverizing an alloy, so the particles 50P have flat portions, acute-angled protrusions, complex fracture surfaces, and the like.
[0038] on the other hand, Figure 3 FIG. 2 is a schematic cross-sectional view of R2-M alloy powder 30 formed by atomization method according to an embodiment of the present invention. Figure 3 As shown, each particle 30P constituting the R2-M alloy powder 30 formed by the atomization method is spherical. Such spherical powder particles 30P are arranged between the surfaces (joining surfaces) 20S of the opposite solid parts 20, and when the surfaces 20S of the solid parts 20 are brought close, they can be rearranged in a manner to uniformly fill the gaps formed by the opposite surfaces 20S. Therefore, unnecessary pores are not formed during joining, and the closeness of the joining surface 20S can be improved.
[0039] Figure 4 It is a stereoscopic view schematically showing the state of the R1-TB system sintered magnet raw materials before joining according to an embodiment of the present invention. In the illustrated example, R1-TB system sintered magnet raw materials 22, 24, and 26 are stacked. A layer of R2-M alloy powder 30 formed by an atomization method is formed between the first R1-TB system sintered magnet raw material 22 located at the lower end and the second R1-TB system sintered magnet raw material 24 located in the center. In addition, a layer of R2-M alloy powder 30 formed by an atomization method is also formed between the second R1-TB system sintered magnet raw material 24 located in the center and the third R1-TB system sintered magnet raw material 26 located at the upper end. Figure 4 In the example, the R2-M alloy powder 30 is coated on the upper surface of the first R1-T-B system sintered magnet raw material 22 and the upper surface of the second R1-T-B system sintered magnet raw material 24. However, the R2-M alloy powder 30 formed by the atomization method can also be coated on the bottom surface of the second R1-T-B system sintered magnet raw material 24 and / or the bottom surface of the third R1-T-B system sintered magnet raw material 26, and can also be coated on the entire surface of the second R1-T-B system sintered magnet raw material and the entire surfaces of the first and third R1-T-B system sintered magnets.
[0040] Figure 5 This is a perspective view schematically showing a state in which R1-TB based sintered magnet raw materials are being joined according to an embodiment of the present invention. Figure 5 In the illustrated state, the first R1-TB system sintered magnet material 22 and the second R1-TB system sintered magnet material 24 are close to each other with the R2-M alloy powder 30 interposed therebetween. The second R1-TB system sintered magnet material 24 and the third R1-TB system sintered magnet material 26 are close to each other with the R2-M alloy powder 30 interposed therebetween.
[0041] In a certain embodiment, pressure can also be applied in the stacking direction. Figure 5The R2-M alloy powder is melted by heat treatment in the state shown, the first R1-TB system sintered magnet raw material 22 is joined to the second R1-TB system sintered magnet raw material 24, and the second R1-TB system sintered magnet raw material 24 is joined to the third R1-TB system sintered magnet raw material 2. In this way, an R-TB system sintered magnet made by integrating these magnet raw materials can be manufactured.
[0042] In this joining process, the rare earth element R2 and the metal element M contained in the R2-M alloy powder 30 diffuse from the joining surfaces of the R1-T-B system sintered magnet raw materials 22, 23, and 24 through the grain boundaries to the inside. The R2-M alloy powder 30 produced by the atomization method not only functions as a diffusion source but also as an excellent joining aid, thereby contributing to the improvement of the joining strength.
[0043] In addition, R2-M alloys such as Pr-Ga alloys have high ductility and generally have poor crushability. Therefore, crushing requires a long time and there are problems with mass production. In an embodiment of the present invention, by using atomized powder of R2-M alloy, powder particles (e.g., particles with a particle size of 200 μm or less) can be obtained without crushing.
[0044] like Figure 6 As illustrated, the manufacturing method of the R-T-B system sintered magnet of the present invention includes: step S10 of preparing a plurality of R1-T-B system sintered magnet raw materials; and step S20 of preparing R2-M alloy powder produced by atomization method. The order of step S10 of preparing a plurality of R1-T-B system sintered magnet raw materials and step S20 of preparing R2-M alloy powder produced by atomization method is arbitrary, and R1-T-B system sintered magnet raw materials and R2-M alloy atomized powder produced in different places can be used respectively.
[0045] The method for producing an RTB system sintered magnet of the present invention further includes: a step S30 of arranging R2-M alloy powder between a plurality of R1-TB system sintered magnet raw materials; and a step S40 of joining the plurality of R1-TB system sintered magnet raw materials.
[0046] Hereinafter, an embodiment of the method for producing an RTB based sintered magnet according to the present invention will be described in more detail.
[0047] 1. Process of preparing raw materials for R1-T-B sintered magnets
[0048] First, a plurality of R1-TB system sintered magnet raw materials are prepared. The R1-TB system sintered magnet raw materials may be any known R1-TB system sintered magnet. A typical example of the R1-TB system sintered magnet raw material that can be used in the present embodiment has the following composition.
[0049] Rare earth element R1: 27.5-35.0 mass%;
[0050] B (a part of B (boron) may be substituted by C (carbon)): 0.80 to 0.99 mass %;
[0051] Ga: 0-0.8 mass%;
[0052] Added metal element M (at least one selected from Al, Cu, Zr, and Nb): 0 to 2 mass %;
[0053] T (a transition metal element mainly including Fe and may contain Co) and inevitable impurities: the remainder.
[0054] In addition, it is preferable that the following inequality (1) is satisfied.
[0055] [T] / 55.85>14[B] / 10.8(1)
[0056] Here, [T] is the content of T expressed in mass %, and [B] is the content of B expressed in mass %.
[0057] The so-called satisfaction of this inequality means that the content of B is less than R2T 14 The stoichiometric composition ratio of the B compound, i.e., the ratio of the B compound to the B compound used to form the main phase (R2T 14 B compound) has a relatively small amount of T.
[0058] By diffusing the R2-M alloy powder into the R1-T-B system sintered magnet material satisfying the formula (1), a higher B can be obtained even without using Dy and Tb. r and H cJ .
[0059] In addition, the rare earth element R1 is mainly a light rare earth element RL (at least one element selected from Nd and Pr), but may also contain heavy rare earth elements such as Dy and Tb. Among them, the usage amount of heavy rare earth elements such as Dy and Tb is preferably less than 2% of the total R1-TB system sintered magnet raw materials, and it is most preferred that the R1-TB system sintered magnet raw materials do not contain heavy rare earth elements such as Dy and Tb (including inevitable impurities).
[0060] In an embodiment of the present invention, Figure 4 In the example shown, the composition of one or both of the first R1-TB system sintered magnet material 22 and the third R1-TB system sintered magnet material 26 is different from the composition of the second R1-TB system sintered magnet material 24 .
[0061] In order to achieve a higher coercive force H than other R1-TB system sintered magnet materials, at least one R1-TB system sintered magnet material among the plurality of R1-TB system sintered magnet materials to be joined has cJ As a heavy rare earth element, a small amount of at least one of Dy and Tb may be contained. For example, when a part of a R1-TB system sintered magnet is required to exhibit a high coercive force H cJ When adding heavy rare earth elements to a part of the R1-TB system sintered magnet raw materials, heavy rare earth elements can be selectively added. However, since it is preferred not to use Dy and Tb as much as possible, the total content of Dy and Tb is preferably less than 5% of the total R1-TB system sintered magnet, more preferably less than 1%, and most preferably no Dy and Tb. The R1-TB system sintered magnet raw materials of the above composition can be manufactured using any known manufacturing method. The R1-TB system sintered magnet raw materials can be products directly after sintering, or they can be cut or ground.
[0062] exist Figure 4 In the example shown, the first and third R1-TB system sintered magnet raw materials 22, 26 can be made thinner than the second R1-TB system sintered magnet raw material 24. For example, the thickness of the first and third R1-TB system sintered magnet raw materials 22, 26 is 2 mm or less (or 1 mm or less), and the thickness of the second R1-TB system sintered magnet raw material 24 can exceed 2 mm (or 1 mm or more).
[0063] 2. Process of preparing R2-M alloy powder produced by atomization method
[0064] (R2) R2 is a rare earth element containing at least one of Nd and Pr, and the total content of Dy and Tb is 50 mass % or less based on the total content of R2.
[0065] For example, when R2 is 80% by mass of the entire R2-M alloy, the total content of Dy and Tb is 40% by mass or less. Preferably, the total content of Dy and Tb is 15% by mass or less relative to the entire R2. Most preferably, the R2-M alloy powder does not contain heavy rare earth elements such as Dy and Tb (including unavoidable impurities). R2 is 65% by mass or more and 97% by mass of the entire R2-M alloy. R2 preferably must contain Pr, and the amount of Pr in R2 is preferably 40% by mass or more, and more preferably 70% by mass or more.
[0066] (M) M is at least one selected from Ga, Cu, In, Al, Sn and Co. M is 3% to 35% by mass of the total R2-M alloy. M preferably must contain Ga, and Ga accounts for 50% or more by mass of M. The R2-M alloy may contain unavoidable impurities. It is most preferred to use an R2-M alloy powder in which Pr accounts for 70% or more by mass of R2 and Ga accounts for 50% or more by mass of M. As a result, Ga can be introduced into the grain boundary between the two grains without almost being introduced into the interior of the main phase crystal grains. By introducing a liquid phase containing Ga into the grain boundary between the two grains, a high H can be obtained even without using Dy and Tb. cJ .
[0067] In an embodiment of the present invention, R2-M alloy powder is produced by an atomization method. The atomization method is a type of powder production method also known as a melt spray method, including well-known atomization methods such as a gas atomization method and a plasma atomization method. For example, by using a gas atomization method, a metal or an alloy is melted in a melting furnace to form a molten liquid, and the molten liquid is sprayed in an inert gas atmosphere such as nitrogen or argon to solidify it. The sprayed molten liquid forms fine droplets and scatters, so it is cooled and solidified at a high speed. The produced powder particles each have a spherical shape, so there is no need to crush them. The size of the powder particles produced by the atomization method is distributed in the range of 10μm to 200μm, for example.
[0068] By using the atomization method, the droplets of the sprayed alloy melt are small, and the surface area is relatively large relative to the weight of each droplet, so the cooling rate becomes high. Therefore, the formed powder particles are amorphous or microcrystalline. In addition, these powder particles can also be additionally heat treated before the joining process to crystallize the amorphous.
[0069] The particle size of the R2-M alloy powder can be adjusted by sieving. In addition, if the powder removed by sieving is within 10 mass %, the influence is small, so it can be used without sieving.
[0070] 3. Step of placing R2-M alloy powder between multiple R1-T-B system sintered magnet raw materials
[0071] The above R2-M alloy powder is arranged between R1-T-B system sintered magnet raw materials (in other words, the R2-M alloy powder is sandwiched by multiple R1-T-B system sintered magnet raw materials). Regarding the arrangement method, the R2-M alloy powder can be arranged by coating the surfaces of two R1-T-B system sintered magnet raw materials, or the R2-M alloy powder can be coated on the surface of only one R1-T-B system sintered magnet raw material. In addition, the R2-M alloy powder can be coated on the entire surface of the R1-T-B system sintered magnet raw material, or it can be coated on the entire surface of the R1-T-B system sintered magnet raw material. Figure 4As shown, only the bonding surface is shown. In addition, two or more R2-M alloy powders with different compositions can also be used. The method of applying R2-M alloy powder on the surface of multiple R1-T-B system sintered magnet raw materials is not limited to a specific coating method. A coating step of applying an adhesive on the surface of the coating object and a step of making the R2-M alloy powder adhere to the area coated with the adhesive can be performed. As adhesives, PVA (polyvinyl alcohol), PVB (polyvinyl butyral), PVP (polyvinyl pyrrolidone) and the like can be listed. When the adhesive is a water-based adhesive, the R-T-B system sintered magnet raw material can be preheated before coating. The purpose of preheating is to remove excess solvent and control the adhesive force, and to uniformly adhere the adhesive. The heating temperature is preferably 60 to 100°C. In the case of an organic solvent-based adhesive with high volatility, this step can also be omitted.
[0072] The method of applying the binder to the surface of the R-TB system sintered magnet raw material may be any method. Specific examples of the application include spraying, dipping, and application using a dispenser. The amount of the binder applied may be, for example, 1.02×10 -5 ~5.10×10 -5 g / mm 2 .
[0073] 4. Process of joining multiple R1-T-B sintered magnets
[0074] According to the present invention, the R1-T-B system sintered magnet raw material and the R2-M alloy powder (atomized powder) are brought into contact with each other and heat treated for bonding. As a result, high bonding strength is achieved, and the grain boundary phase of the R1-T-B system sintered magnet is completely modified throughout the magnet, thereby achieving high B r and H cJ .
[0075] The heat treatment for joining can be carried out at a temperature of 450°C to 1000°C for a time of 5 minutes to 720 minutes. The heat treatment can also be carried out at a relatively high temperature (700°C to 1000°C) and then at a relatively low temperature (450°C to 600°C) (two-stage heat treatment). Preferred conditions include: heat treatment at 730°C to 980°C for about 5 minutes to 500 minutes, cooling (after cooling to room temperature, or cooling to 440°C to 550°C), and then heat treatment at 440°C to 550°C for about 5 minutes to 500 minutes. The atmosphere gas for the heat treatment can be nitrogen or an inert gas. The atmosphere gas can also be decompressed.
[0076] Example
[0077] The present invention will be described in more detail using examples, but the present invention is not limited thereto.
[0078] Experimental Example 1
[0079] Each element is weighed so that the raw material of the R1-T-B system sintered magnet has a composition approximately as shown in No. 1-A and 1-B in Table 1, and is cast by a thin strip continuous casting method to obtain a thin flaky alloy. The obtained thin flaky alloy is hydrogen embrittled in a hydrogen pressurized atmosphere, heated to 550°C in a vacuum, cooled, and subjected to a dehydrogenation treatment to obtain a coarsely pulverized powder. Next, 0.04% by mass of zinc stearate as a lubricant is added to the obtained coarsely pulverized powder relative to 100% by mass of the coarsely pulverized powder and mixed, and then dry-pulverized in a nitrogen atmosphere using an air flow pulverizer (jet mill device) to obtain a particle size D 50 The alloy powder is 4.3μm. To the above alloy powder, 0.3% by mass of liquid lubricant is added relative to 100% by mass of finely pulverized powder and mixed, and then molded in a magnetic field to obtain a molded body. Among them, the molding device uses a so-called right-angle magnetic field molding device (transverse magnetic field molding device) in which the direction of magnetic field application is orthogonal to the direction of pressurization. The obtained molded body is sintered in a vacuum at a temperature of not less than 1000°C and not more than 1050°C (for each sample, a temperature that fully causes densification through sintering is selected) for 4 hours to prepare a plurality of R1-T-B series sintered magnet raw materials (No. 1-A and 1-B). The density of the sintered magnet is 7.5Mg / m 3 The above. In addition, the obtained R1-T-B system sintered magnet raw material was machined to a length of 10 mm × width of 5 mm × thickness of 3 mm (thickness is in the magnetization direction). The results of the composition of the obtained R1-T-B sintered magnet raw material are shown in Table 1. Among them, each component in Table 1 was measured using high-frequency inductively coupled plasma optical emission spectrometry (ICP-OES). In addition, the R1-T-B system sintered magnet raw materials all satisfy inequality (1).
[0080] [Table 1]
[0081]
[0082] Next, an alloy powder having the composition shown in No. 1-a of Table 2 is prepared by an atomization method, thereby preparing R2-M alloy powder. The particle size of the obtained R2-M alloy powder is less than 106 μm. Then, each element is weighed to make an alloy having the composition shown in No. 1-b of Table 2, and the alloy is cast by a thin strip continuous casting method to obtain a flaky alloy. The obtained flaky alloy is hydrogen embrittled in a hydrogen pressurized atmosphere, heated to 550°C in a vacuum, cooled, and dehydrogenated to obtain a coarsely pulverized powder. To the obtained coarsely pulverized powder, 0.04 mass% of zinc stearate as a lubricant is added to 100 mass% of the coarsely pulverized powder and mixed, and then dry-pulverized in a nitrogen atmosphere using an air flow pulverizer (jet mill device) to obtain a particle size D 50 The alloy powder is 4.3 μm.
[0083] [Table 2]
[0084]
[0085] Next, the binder was applied to the entire surface of the R1-T-B system sintered magnet raw materials No. 1-A and 1-B in Table 1. Regarding the coating method, the R1-T-B system sintered magnet raw materials were heated to 60°C on a hot plate, and then the binder was applied to the R1-T-B system sintered magnet raw materials by a spray method. PVP (polyvinyl pyrrolidone) was used as the binder.
[0086] Next, the diffusion source (R2-M alloy powder) of No. 1-a in Table 2 is attached to the R1-T-B system sintered magnet raw material (No. 1-A and 1-B) coated with a binder. Regarding the attachment method, the diffusion source is spread in a container, and after the R1-T-B system sintered magnet raw material coated with a binder is cooled to room temperature, the diffusion source is attached in a manner that it is spread over the entire surface of the R1-T-B system sintered magnet raw material in the container.
[0087] Next, the R1-T-B sintered magnet raw materials (No. 1-A and 1-B) were in contact with the R2-M alloy powder (No. 1-a), and the R1-T-B sintered magnet raw materials No. 1-A and 1-B were overlapped in the thickness (3 mm) direction (surfaces of 10 mm in length × 5 mm in width were in contact with each other), and heat treatment was performed to join the R1-T-B sintered magnet raw materials to obtain the R-T-B sintered magnet (No. 1-1). Regarding the heat treatment, the heat treatment was performed at 900°C for 8 hours, cooled to room temperature, and then heat treated at 500°C for 6 hours (two-stage heat treatment). In the same manner, the diffusion source No. 1-b in Table 2 is attached to the R1-T-B system sintered magnet raw materials (No. 1-A and 1-B), and heat treatment is performed in the same manner to join the R1-T-B system sintered magnet raw materials to obtain the R-T-B system sintered magnet (No. 1-2).
[0088] The generation of pores was confirmed on the joint surface of the obtained R-T-B system sintered magnet. If there are many pores, there is a possibility that the bonding strength will decrease and peeling will occur starting from the pores. Therefore, especially when the R-T-B system sintered magnet is used in electric motors that need to rotate at high speed, it is necessary to suppress the generation of pores.
[0089] The R-T-B system sintered magnets (No. 1-1 and 1-2) were cut and polished by machining, and the cross-section of any joined magnet including the joining surface (magnet cross-section with a width of 5 mm and a thickness of 6 mm) was observed by a scanning electron microscope (SEM: JCM-7001F manufactured by JEOL Ltd.). The observation area was 500 μm × 500 μm, and the generation of pores on the joining surface was confirmed by visual inspection. The generation of pores of less than 10% of the joining surface (100 × the area of the pore portion / the area of the joining portion) is regarded as the present invention. The results are shown in Table 3. The case where the generation of pores is less than 10% is recorded as 0, and the case where it exceeds 10% is recorded as ×. Then, the results of the magnetic properties of the R-T-B system sintered magnets are shown in Table 3. The magnetic properties were measured using a B-H tracer.
[0090] [Table 3]
[0091]
[0092] As shown in Table 3, the examples of the present invention suppressed the generation of pores, whereas the comparative examples (the case of using diffusion sources produced by the strip casting method) did not suppress the generation of pores.
[0093] Experimental Example 2
[0094] In the same manner as in Experimental Example 1, prepare R1-T-B system sintered magnet raw materials so that they have approximately the composition shown in No. 2-A and 2-B of Table 4. The obtained R1-T-B system sintered magnet raw materials are machined to form a length of 10 mm × width of 5 mm × thickness of 3 mm (thickness is in the magnetization direction). The results of the composition of the obtained R1-T-B sintered magnet raw materials are shown in Table 4. Among them, each component in Table 4 is measured using high-frequency inductively coupled plasma optical emission spectrometry (ICP-OES). Then, prepare R1-T-B system sintered magnet raw materials No. 1-A and 1-B of Experimental Example 1.
[0095] [Table 4]
[0096]
[0097] Next, alloy powders having compositions shown in Nos. 2-a to 2-e of Table 5 were prepared by atomization to prepare R2-M alloy powders. Then, R2-M alloy powders of No. 1-a of Experimental Example 1 were prepared. The particle size of the obtained R2-M alloy powders was 106 μm or less.
[0098] [Table 5]
[0099]
[0100] Next, the R1-T-B system sintered magnet raw materials were joined in the same manner as in Experimental Example 1 under the conditions shown in Table 6 to obtain an R-T-B system sintered magnet. As for No. 2-1 in Table 6, a binder was applied to the entire surface of the R1-T-B system sintered magnet raw materials of No. 1-A and 1-B in the same manner as in Experimental Example 1, and the R-2M alloy powder of No. 2-a was attached to the R1-T-B system sintered magnet raw materials (No. 1-A and 1-B) coated with the binder in the same manner as in Experimental Example 1. Next, the R1-T-B system sintered magnet raw materials No. 1-A and 1-B were overlapped in the thickness direction (3 mm) in a state where the R1-T-B system sintered magnet raw materials (No. 1-A and 1-B) were in contact with the R2-M alloy powder (No. 2-a), and heat treatment was performed in the same manner as in Experimental Example 1, thereby joining the R1-T-B system sintered magnet raw materials to obtain an R-T-B system sintered magnet (No. 2-1). No. 2-2 to 2-7 are also described in the same manner. For the obtained R-T-B system sintered magnet, the same operation as in Experimental Example 1 was performed, and the generation of pores on the joining surface was confirmed by visual inspection. Then, the magnetic properties of the R-T-B system sintered magnet were measured. The results are shown in Table 6.
[0101] [Table 6]
[0102]
[0103] As shown in Table 6, the examples of the present invention all suppressed the generation of pores.
[0104] Industrial Applicability
[0105] By using the present invention, it is possible to produce r and high H cJ The sintered magnet of the present invention is suitable for various motors such as motors for hybrid vehicles and household electrical appliances that are exposed to high temperatures.
[0106] Explanation of symbols
[0107] 12. R2T included 14 Main phase of B compound; 14. Grain boundary phase; 14a. Two-grain grain boundary phase; 14b. Grain boundary triple point; 20. Solid component; 30. R2-M alloy powder; 22, 24, 26. R1-T-B series sintered magnet raw materials; 50. Alloy powder.
Claims
1. A method for producing an R-T-B system sintered magnet, characterized in that: include: The process of preparing multiple R1-T-B system sintered magnet raw materials with different compositions, Wherein, R1 is a rare earth element including at least one of Nd and Pr, and T is a transition metal element mainly composed of Fe; A step of preparing an R2-M alloy powder containing 65 mass % to 97 mass % of R2 and 3 mass % to 35 mass % of M by an atomization method, Wherein, R2 is a rare earth element containing at least one of Nd and Pr, R2 must contain Pr, and the amount of Pr in R2 is 70 mass % or more, M is at least one selected from Ga, Cu, In, Al, Sn and Co, M must contain Ga, and the amount of Ga in M is 50 mass % or more; The step of arranging R2-M alloy powder between the plurality of R1-T-B system sintered magnet raw materials includes: a preheating step of preheating the plurality of R1-TB system sintered magnet raw materials to 60°C to 100°C before applying the binder, On the surface of each of the plurality of R1-TB based sintered magnet materials, a 1.02×10 -5 ~5.10×10 -5 g / mm 2 The coating process of applying the adhesive with a coating amount of a step of attaching the R2-M alloy powder to the regions of the plurality of R1-TB based sintered magnet raw materials to which the binder is applied, a step of overlapping the plurality of R1-TB system sintered magnet raw materials in a thickness direction with the R2-M alloy powder disposed between the plurality of R1-TB system sintered magnet raw materials; and A joining step of making the rare earth element R2 and the metal element M contained in the R2-M alloy powder diffuse from the joining surfaces of the plurality of R1-TB system sintered magnet raw materials through the grain boundaries into the interior of each of the plurality of R1-TB system sintered magnet raw materials at a temperature of not less than 450° C. and not more than 1000° C., The R2-M alloy powder does not contain heavy rare earth elements. The R2-M alloy powder is heat treated before the bonding step to crystallize amorphous materials in the powder particles.
2. The method for producing an R-T-B system sintered magnet according to claim 1, wherein: The T further includes Co.
3. The method for producing an R-T-B system sintered magnet according to claim 1 or 2, characterized in that: The plurality of R1-TB system sintered magnet raw materials include a first R1-TB system sintered magnet raw material having a relatively high coercive force and a second R1-TB system sintered magnet raw material having a relatively low coercive force.
4. The method for producing an R-T-B system sintered magnet according to claim 3, wherein: At least one of the first R1-TB system sintered magnet material and the second R1-TB system sintered magnet material has a thickness of 2 mm or less.
5. The method for producing an R-TB system sintered magnet according to claim 3, wherein: At least one of the first R1-TB system sintered magnet material and the second R1-TB system sintered magnet material has a thickness of 1 mm or less.
Citation Information
Patent Citations
Bonded body of permanent magnet and member of different kind of material and bonding method
JP1996116633A
RFeB-BASED MAGNET AND PRODUCTION METHOD THEREFOR
JP2015073045A
R-T-B-based rare earth sintered magnet and method of manufacturing same
CN106024236A
Preparation method for permanent magnet material with low content of heavy rare earth and high coercivity
CN106601464A
Alloy for R-T-B-based rare earth sintered magnet and manufacturing method thereof, and manufacturing method of R-T-B-based rare earth sintered magnet
CN106847454A